Drugs in Treatment of Developmental Dyslexia - J Gordon Millichap (Pediatric Neurology Briefs)
An acute 2 day trial of methylphenidate (10 mg) and of meclizine (12.5 mg) and a 6 month crossover placebo-controlled chronic trial of meclizine (12.5 mg) in children with developmental dyslexia are reported from the University of Calgary, Alberta, Canada.